The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ani9050201
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effects of Insects in Feed on Poultry Growth Performances

Abstract: We investigated and summarized results from studies evaluating the effects of feeding poultry with insects on their growth performances. After a systematic review of studies published since 2000, two independent reviewers assessed the eligibility of each one based on predefined inclusion criteria. We extracted information on the study design, insects, avian species, and growth performances, i.e., average daily gain, feed intake, and feed conversion ratio. Next, we estimated pooled differences between performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 49 publications
2
34
1
2
Order By: Relevance
“…On the other hand, the converse results were reported in another in vitro digestibility study that HI was higher CPd than TM (Marono et al, 2015). Contrary to expectation, grasshopper (PS) represented the high CPd based on in vitro digestibility in this study which the using grasshopper in feed formulation influenced on lower average daily weigh gain of poultry (Moula & Detilleux, 2019). Therefore, the results from in vitro digestibility testing should be used as one of considerate information which should further consider on palatability and amino acid profiles.…”
Section: Ta B L E 3 (Continued)contrasting
confidence: 70%
“…On the other hand, the converse results were reported in another in vitro digestibility study that HI was higher CPd than TM (Marono et al, 2015). Contrary to expectation, grasshopper (PS) represented the high CPd based on in vitro digestibility in this study which the using grasshopper in feed formulation influenced on lower average daily weigh gain of poultry (Moula & Detilleux, 2019). Therefore, the results from in vitro digestibility testing should be used as one of considerate information which should further consider on palatability and amino acid profiles.…”
Section: Ta B L E 3 (Continued)contrasting
confidence: 70%
“…Zadeh et al [9] reported similar observations for quails fed with a basal diet supplemented with TM. In contrast, Bovera, et al [2] observed the highest weight of carcass in broilers fed with TM larvae meal as a protein source due to their high protein quality and quantity [13]. It is noteworthy that the liver yield was significantly higher in the group that received OL alone, when compared to the other groups (Table 4).…”
Section: Resultsmentioning
confidence: 87%
“…In 2014 the first international conference on "Insects to feed the world" was organized by the FAO [13] which proposed, from the first time, the use of insects as promising alternative food and feed sources as a possible solution related to the expected demographic growth. Since that time, a new research field has emerged and an impressive number of articles have been published (see reviews of [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]), with an exponential increase in scientific knowledge on insects as feed.…”
Section: Insects As Feed Ingredientmentioning
confidence: 99%